Competitive deviance from ethicality: A focus on online settings - Şahin-Kazazoğlu, G.N.; Özçelik, A.B.; Burnaz, Ş. (Springer Nature, 2019)
As spreading the information becomes easier with online technologies, consumers are able to both share their experiences and collect other users’ experiences. This may lead to affect the purchase decision of others who are exposed to online reviews. Hence, behaving deviant, the companies can use the power of online reviews for the benefit of themselves by manipulating the review content. In order to attract customers, companies can write positive reviews for their own business or negative reviews for those of competitors. However, consumers are getting aware of these devious moves day by day and they evaluate the believability of the online reviews in a more suspicious manner. This chapter proposes a conceptual model on the outcomes of perceived believability and perceived deviancy in online reviews, in terms of perceived ethicality of the company. The outcomes of the study are expected to provide a novel approach to the online competition strategy through consideration of the long-term value co-destruction for organizations in the competitive marketplace. © 2019, Springer Nature Singapore Pte Ltd.
Keywords: Competitive Deviance; Deviant Behavior; Ethics; Online Review; Perceived Ethically